Investigation of Crystalluria and Its Association with Urinary Tract Infections - Zia, Hafza; Zhaira, Ismat; Noor, Malaika; Bibi, Aliya; Jabeen, Shanza; Khadija; Khan, Malaika Anwar; Nasir, Shumail; Jabeen, Sidra; Zhaira, Dua (Indus Journal of Bioscience Research, 2024)
Background: Crystalluria, the presence of crystals in urine, can arise from factors such as dehydration, dietary habits, and metabolic disorders, often linked to urinary tract infections (UTIs). Objective: This study aims to identify the predominant types of crystals in patients with UTIs and examine the association between pus cells and crystalluria. Conducted at Alkhidmat Razi Hospital over four months (June-September 2024), it utilized a non-probability purposive sampling technique. Methods: A total of 134 UTI patients were enrolled, with 35.1% male and 64.9% female participants. Age groups were categorized into six ranges: 5-15, 15-25, 26-35, 36-45, 46-55, and 56-65 years. The mean age was 34.1±16.4 years. Results indicated that 31% had crystalluria while 69% did not. Notably, 68.7% of samples showed no detectable crystals. Results: Calcium oxalate emerged as the most common crystal type, found in 25.4% of cases. Males exhibited higher percentages of crystalluria, with calcium oxalate present in 17.9% of males versus 7.47% of females. Other crystals included amorphous phosphate (2.24% in males and 1.49% in females) and calcium carbonate (0.75% in males only). Conclusion: Understanding the specific types of crystals and their impact on UTI severity is vital for treatment strategies. Statistical analysis via SPSS version 25.0 revealed a chi-square p-value of 0.313, indicating no significant association between pus cells and crystalluria.